Economic modelling of diagnostic and treatment pathways in National Institute for Health and Care Excellence clinical guidelines : the ModellingAlgorithm Pathways in Guidelines (MAPGuide) project /: the ModellingAlgorithm Pathways in Guidelines (MAPGuide) project. (December 2013) - Lord, J
No abstract available